Early surgical decompression within 8 hours for traumatic spinal cord injury: Is it beneficial? A meta-analysis - Dong-Yeong Lee; Young-Jin Park; Hyun-Jung Kim; Hyeong-Sik Ahn; Sun-Chul Hwang; Dong-Hee Kim (Acta Orthopaedica et Traumatologica Turcica, 2018)
Introduction: The aim of this study is to evaluate whether early (<8 h) surgical decompression is better in improving neurologic outcomes than late (≥8 h) surgical decompression for traumatic spinal cord injury (tSCI). Methods: The various electronic databases were used to detect relevant articles published up until May 2016 that compared the outcomes of early versus late surgery for tSCI. Data searching, extraction, analysis, and quality assessment were performed according to Cochrane Collaboration guidelines. The results are presented as relative ratio (RR) for binary outcomes and mean difference (MD) for continuous outcomes with 95% confidence intervals (CIs). Results: Seven studies were finally included in this meta-analysis. There were significant differences between the 2 groups in neurologic improvement (MD = 0.54, 95% CI = −18.52 to −7.02, P < 0.0001) and length of hospital stay (MD = −12.77, 95% CI = 0.34–0.74, P < 0.00001). However, no significant differences were found between the 2 groups in perioperative complications (OR = 0.95, 95% CI = 0.35–2.61, P = 0.92). Conclusions: Early surgical decompression within 8 h after tSCI was beneficial in terms of neurologic improvement compared with late surgery. Early surgical decompression (within 8 h) is recommended for patients with tSCI. Level of evidence: Level III, therapeutic study. Keywords: Spinal cord injuries, Decompression, Timing of surgery, Meta-analysis